تمويل الأوراق المالية بالهامش في ظل التعليمات رقم (7) لسنة 2013 الصادرة عن هيئة سوق رأس المال الفلسطينية - أبو حاج، عيسى (مركز جيل البحث العلمي, 2021)
تناول هذا البحث التمويل بالهامش كأحد أسس تمويل الأوراق المالية في سوق فلسطين للأوراق المالية المرخص من قبل هيئة سوق رأس المال الفلسطينية لتداول الأوراق المالية. اشتمل هذا البحث على فرعين؛ تناول الفرع الأول ماهية التمويل بالهامش كأحد أسس تمويل الأوراق المالية وتكييفه القانوني. توصل الباحث إلى أن التمويل بالهامش ينطوي على نوعين من المعاملات: البيع القصير والشراء على الهامش. واتضح بأن البيع القصير قد يكون مكشوف وذلك حينما لا يملك البائع الورقة المالية حين البيع وهذه الفكرة محظورة في بعض الأنظمة القانونية. وقد يكون البيع القصير بيع مغطى بحيث يقترض المستثمر الورقة المالية من شركة الوساطة ومن ثم يقوم ببيعها. في حين، أن الشراء على الهامش ينطوي على قيام المستثمر بتغطية جزء من قيمة الورقة المالية وتقوم شركة الأوراق المالية بتغطية الجزء الأخر منها. تبني القانون الفلسطيني الشراء بالهامش كأحد صور التمويل بالهامش وذلك بموجب التعليمات رقم (7) لسنة 2013 الصادرة عن هيئة سوق رأس المال الفلسطينية بما لها من صلاحيات بموجب قانون الأوراق المالية الفلسطيني رقم (12) لسنة 2004. وتناول الباحث بالفرع الثاني: المتطلبات القانونية لعملية التمويل بالهامش وتوصل الباحث إلى أن القانون الفلسطيني ألزم شركة الأوراق المالية أن تقوم بإبرام اتفاقية تمويل مع المستثمر، والزمها أيضا بجملة من الواجبات التعاقدية بحيث تلتزم بإعلام المستثمر وتبصيره بطبيعة العقد المزمع إبرامه والمخاطر المصاحبة له.
This research addresses "Margin financing" as method of financing securities in the Palestine Stock Exchange market, which is licensed by the Palestinian Capital Market Authority for securities trading. This research is composed of two sections; the first section addressed the legal concept of margin financing and its legal appraisal. We concluded that the margin financing involves two types of transactions: short selling and buy on margin. It became clear that the short sale may be in doubt when the seller does not own the securities at the time of sale; this transaction is prohibited in several legal systems. On the other hand, the short sale may be a covered sale; in this transaction, the investor borrows the security from the brokerage company and then sells it. Palestinian law has appraised buy on margin as form of margin financing this is in accordance with the instructions no. (7) Of 2013 issued by the Palestinian Capital Market Authority with its competence under the Palestinian Securities Law No. (12) Of 2004. The second section identifies the legal requirements for the margin financing transactions, we concluded that the Palestinian law obliged the securities company to conclude a financing agreement with the investor, and also obligated it with a several of contractual duties where the company is obligated to inform the investor and enlighten him regards the nature of the contract and the risks surrounding this transaction.
Keywords: الأسواق المالية -- التمويل بالهامش -- المعاملات المالية -- الاقتصاد الفلسطيني